The Implication Of Instagram Visual Content On Interest In Visiting Santirah River Tubing, Tulisari Village, Pangandaran Regency - Akib Hehanussa; Mappiasse; Hersanius Kurnia Peong; Laurensius Sandrio (Pusat Penelitian dan Pengabdian Masyarakat Politeknik eLBajo Commodus, 2024)
This research aims to analyze the implications of Instagram visual content on interest in visiting the Santirah River Tubing tourist destination, Raburi Village, Parigi District, Pangandaran Regency. The method used in this research is a quantitative method which uses descriptive analysis. The information collection technique used was distributing questionnaires randomly via Google Form. Observation and documentation methods are also used to obtain relevant information. The data processing technique is carried out through testing the validity and reliability of the questionnaire that has been distributed. After the data is valid and reliable as a whole and per statement item, a normality test is carried out. From the results of data processing, it was concluded that Instagram visual content (X) had a significant effect on visiting interest (Y) at Santirah River Tubing (SRT) by 78.4%. In another sense, hypothesis H1 is accepted, meaning that there is a significant influence between the Instagram visual content variable (X) on visiting interest (Y) at SRT, Selalari Village, Parigi District, Pangandaran Regency.